Analisis Pengaruh Pengalaman dan Karakter Sumber Daya Manusia Terhadap Kualitaskerjaan Proyek Konstruksi: Studi Kasus: Kecamatan Kuta Alam dan Syiah Kuala - Bunyamin; Heru Pramanda; Wahyu Diara; David Sarana (Tameh, 2024)
Quality of work is a result that can be measured by the effectiveness and efficiency of a job performed by human resources. There are many factors that can affect the quality of work, one of which is experience and character. independent variable and the dependent variable. In this study, the independent variables consisted of experience (X1) and character (X2), while the dependent variable was work quality (Y). The purpose of this study was to determine the influence and character of human resources on the quality of construction project work in Central Aceh District. The formulation of the problem of this research is how to determine the relationship between the Data processing uses the descriptive statistical data analysisthod through the SPSS application. The research results obtained from the validity test of each question item stated that all were valid. The influence of experience and character when viewed from the highest frequency value is 50.0%, which has a very influential impact. While the highest frequency value for the quality of work is 36.7%. The hypothesis test of the variable f test has a (simultaneous) effect on the independent variable. The multiple determination coefficient test (R2) obtained a value of R2 = 0.782, meaning that the experience and character of the management consultant jointly affect the quality of work. For the partial determination coefficient test, it is known that the effective contribution of the character variable is 31.9%, the character variable has more influence on the quality of work in project work in Central Aceh District than the experience variable.